Learning objectives, task setting and differentiation : Mastering teaching skills series - Kerry, Trevor (United kingdom : Nelson Thornes, 2002)
Offering practical support, these books combine background theory with realistic advice. Activities, taken from real-life examples, help users to implement and develop practical skills. Linkied to the governement based standards framework, this series will be valuable to teachers undergoing Continuing Professional Development.
includes index.
Keywords: Teaching -- Great Britain; Teaching -- Practice -- Great Britain; Teaching